The Informed Patient : A Complete Guide to a Hospital Stay - Friedman, Karen A.; Merwin, Sara L. (Book collections on Project MUSE., 2017)
Even the most capable individuals are challenged when confronted with the complexity of the modern hospital experience. The Informed Patient is a guide and a workbook, divided into topical, focused sections with step-by-step instructions, insights, and tips to illustrate what patients and their families can expect during a hospital stay. Anyone who will experience a hospital stay--or friends or family who may be in charge of a patient's care--will find all the help and advice they could need in the detailed sections that cover every aspect of what they can expect. Karen A. Friedman, MD, and Sara L. Merwin, MPH, offer hands-on advice about how patients, health care providers, and medical staff can work together to achieve good outcomes. Through anecdotes, tips, sidebars, and clinical scenario vignettes, The Informed Patient presents ways to enhance and optimize a hospital stay, from practical advice on obtaining the best care to dealing with the emotional experience of being in the hospital.